# Class 11 RD Sharma Solutions – Chapter 20 Geometric Progressions- Exercise 20.5 | Set 2

### Question 12. If (a – b), (b – c), (c – a) are in G.P., then prove that (a + b + c)^{2} = 3(ab + bc + ca)

**Solution: **

Given: (a – b), (b – c), (c – a) are in G.P.

Attention reader! All those who say programming isn't for kids, just haven't met the right mentors yet. Join the

Demo Class for First Step to Coding Course,specificallydesigned for students of class 8 to 12.The students will get to learn more about the world of programming in these

free classeswhich will definitely help them in making a wise career choice in the future.(b – c)

^{2}= (a – b)(c – a)b

^{2}+ c^{2}– 2bc = ac – a^{2}– bc + abb

^{2}+ c^{2}+ a^{2}= ac + bc + ab -(1)Now,

(a + b + c)

^{2}= a^{2}+ b^{2}+ c^{2}+ 2ab + 2bc + 2ca= ac + bc + ab + 2ab + 2bc + 2ca

So, using eq(1), we get

= 3ab + 3bc + 3ca

(a + b + c)

^{2}= 3(ab + bc + ca)LHS = RHS

Hence, proved

### Question 13. If a, b, c are in G.P., then prove that:

**Solution: **

Given: a, b, c are in G.P.

So, a, b = ar, c = ar

^{2}1/r = 1/r

L.H.S = R.H.S

Hence, proved

### Question 14. If the 4^{th}, 10^{th}, and 16^{th} terms of a G.P. are x, y, and z respectively. Prove that x, y, z are in G.P.

**Solution: **

Let us considered the 4

^{th}term = ar^{3}10

^{th}term = ar^{9}16

^{th}term = ar^{15}So, ar

^{9}= = ar^{9}Therefore, 4

^{th}, 10^{th}, 16^{th}terms are also in G.P.Hence, proved

### Question 15. If a, b, c are in A.P. and a, b, d are in G.P., then prove that a, a – b, d – c are in G.P.

**Solution:**

Given: a, b, c are in A.P.

2b = a + c -(1)

also,

a, b, d are in G.P., so

b

^{2}= ad -(2)Now,

(a – b)

^{2}= a^{2}+ b^{2}– 2ab= a

^{2}+ ad – a(a + c)From eq(1) and (2), we get

= a

^{2}+ ad – a^{2}– ac= ad – ac

(a – b)

^{2}= a(d – c)(a – b)/a = (d – c)/(a – b)

Hence, proved a, (a – b), (d – c) are in G.P.

### Question 16. If p^{th}, q^{th}, r^{th} and s^{th} terms of an A.P. be in G.P., then prove that p – q, q – r, r – s are in G.P.

**Solution:**

Let us considered R be common ratio,

Given: a

_{p}, a_{q}, a_{r}, a_{s}of AP are in GPR =

Now,

Using eq(1) and (2), we get

Hence, proved (p – q), (q – r), (r – s) are in G.P.

### Question 17. If are the three consecutive terms of an A.P., prove that a, b, c are the three consecutive terms of a G.P.

**Solution:**

Given: \frac{1}{a+b},\frac{1}{2b},\frac{1}{b+c} are in A.P.

ab + ac + b

^{2}+ bc = 2b^{2}+ bc + bab

^{2}+ ac = 2b^{2}b

^{2}= acHence, proved a, b , c are in G.P.

### Question 18. If x^{a} = x^{b/2} z^{b/2} = z^{c}, then prove that 1/a, 1/b, 1/c are in A.P.

**Solution:**

b/2a + b/2c = 1

1/a + 1/c = 2/b

Hence, 1/a, 1/b, 1/c are in A.P.

### Question 19. If a, b, c are in A.P., b, c, d are in G.P. and 1/c, 1/d, 1/e are in A.P., prove that a, c, e are in G.P.

**Solution:**

Given: a, b, c are in A.P.

2b = a + c -(1)

Also, b, c, d are in G.P.

c

^{2}= bd -(2)1/c, 1/d, 1/e are in A.P.

2/d = 1/c + 1/e -(3)

We need to prove that

a, b, c are in G.P.

c

^{2}= aeNow,

c

^{2}(c + e) = ace + c^{2}ec

^{3 }+ c^{2}e = ace + c^{2}ec

^{3 }= acec

^{2 }= aeHence, proved.

### Question 20. If a, b, c are in A.P. and a, x, b and b, y, c are in G.P., show that x^{2}, b^{2}, y^{2} are in A.P.

**Solution:**

Given: a, b, c are in A.P.

2b = a + c -(1)

Also, a, x, b are in G.P.

x = ab -(2)

and b, y, c are in G.P.

y

^{2}= bc -(3)Now

2b

^{2}= x^{2}+ y^{2}= (ab) + (bc) -(By using eq(2) and (3))

2b

^{2}= b(a + c)2b

^{2}= b(2b) -(By using eq(1))2b

^{2}= 2b^{2}L.H.S = R.H.S

2b

^{2}= x^{2}+ y^{2}Hence, x

^{2}, b^{2}, y^{2}are in A.P.

### Question 21. If a, b, c are in A.P. and a, b, d are in G.P., show that a, (a – b), (d – c) are in G.P.

**Solution:**

Given: a, b, c are in A.P.

2b = a + c -(1)

Also, a, b, d are in G.P.

b

^{2}= ad -(2)Now

(a – b)

^{2}= a(d – c) -(By using eq(2))a

^{2}– 2ab = -aca

^{2}– 2ab = ab – aca(a – b) = a(b – c)

a – b = a – c

2b = a + c

a + c = a + c, -(By using eq(1))

L.H.S = R.H.S

Hence, a, (a – b), (d – c) are in G.P.

### Question 22. If a, b, c are three real numbers in G.P. and a + b + c = xb, then prove that either x < -1 or x > 3.

**Solution:**

Let us considered r be the common ratio of G.P.

So, a, b = ar, c = ar

^{2}a + b + c = xb

a + ar + ar

^{2}= x(ar)a(1 + r + r

^{2}) = x(ar)r

^{2}+ (1 – x)r + 1 = 0Here, r is real, so

D ≥ 0

(1 – x)

^{2}– 4(1)(1) ≥ 01 + x

^{2}-2x – 4 ≥ 0x

^{2}– 2x – 3 ≥ 0(x – 3)(x + 1) ≥ 0

Hence, x < -1 or x > 3

### Question 23. If p^{th}, q^{th} and r^{th} terms of a A.P. and G.P. are both a, b and c respectively, show that a^{b-c} b^{c-a} c^{a-b} = 1.

**Solution:**

Let us considered the A.P. be A, A + D, A + 2D, …. and G.P. be x, xR, xR

^{2},Then

a = A + (p – 1)D, B = A + (q – 1)D, c = A + (r – 1)D

a – b = (p – q)D, b – c = (q – r)D, c – a = (r – p)D

Also a = XR

^{p-1}, b = xR^{q-1}, c = xR^{r-1}Hence, a

^{b-c}.b^{c-a}.c^{a-b }= (xR^{p-1})^{(q-r)D}.(xR^{q-1})^{(r-p)D}.(xR^{r-1})^{(p-q)D}= x

^{(q-r+r-p+p-q)D}.R^{[(p-1)(q-r)+(q-1)(r-p)+(r-1)(p-q)]D}= x

^{0}.R^{0}= 1.1

= 1